Evaluation of Reserves for Improving the Efficiency of Using Rolling Stock of a Motor Transport Enterprise - Khavruk, V. O (Science and Transport Progress, 2022)
Purpose. The work is aimed to analyze the components of the target function of reducing costs for the operation and maintenance of motor vehicles (buses) and determine the optimal periodicity of planned repairs. Methodology. The research was carried out using general scientific methods: analysis and synthesis, abstraction and concretization, induction and deduction, system analysis. Findings. In order to estimate reserves for improving the efficiency of rolling stock, the target function of minimizing costs (losses) during the operation of motor vehicles using the example of buses is given, which includes two aggregated component costs for planned activities after maintenance of motor vehicles and resources used to eliminate the consequences of unplanned repairs, including losses caused by them. Exponential dependencies of the number of unplanned repairs per calendar year of operation of motor vehicles obtained as a result of processing an array of statistical data on the enterprise are presented. It was found that one of the ways to improve the efficiency of the rolling stock of the motor vehicle enterprise is to reduce downtime due to current unplanned repairs. For this purpose, it is proposed to carry out planned repairs of each moving unit of motor vehicles. The graphical dependence of the number of unscheduled repairs on the amount of bus mileage between repairs is shown for a specific motor vehicle enterprise. Calculations of the components of the target function of increasing the use efficiency of buses were performed, and the optimal inter-repair mileage for carrying out planned repairs during the calendar year was determined graphically. The economic component of increasing the efficiency of use of the rolling stock of the automobile enterprise is substantiated – the lack of income from unfulfilled transport work, which is characterized by the average load of motor vehicles. Using the example of buses, it was found that the average load is directly proportional to the number of transported passengers and inversely proportional to the mileage along the route. Originality. All components of the target function of minimizing the total costs of planned activities after technical maintenance and resources of unplanned repairs, including losses (damages) from downtime, are thoroughly considered. Practical value. The results of the performed research can be used by motor transport companies to determine the optimal intervals between repairs. Carrying out planned repairs of each motor vehicle will make it possible to reduce losses from idle time and increase the use efficiency of rolling stock as a whole.